Մխիթարյանների հետ Շահամիրյանների մատենագրական առնչությունների պատմությունից («Բառգիրք Հայկազեան լեզուի»-ն իբրև «Նոր տետրակի» աղբյուր) - Պողոս Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
В арменоведении проведены серьезные исследования в оценке армянского патриотического кружка Мадраса и особенно деятельности Шаамирянов. Их литературное наследие по праву считалось вершиной армянской политической мысли с последней трети XVIII в.—до Хачатура Абовяна. The assessment of the activities of the Madras Armenian national loyalty group, the Shahamirians and their literary heritage in particular, was the subjcct of a serious research in Armenology. Their service was rightly considered as the highlight of the Armenian political thinking in the last 30 years of the 18th century, right before the advent of Khachatur Abovian.
Keywords: History; Philology; Linguistics; Language and Literature; D History